How is the Human Rights based approach to change the ethics and praxis of achieving Universal Health Coverage? - Claudio Schuftan (Social Medicine Publication Group, 2016)
Much is being said these days about Universal Health Coverage (UHC). The UN Secretary General is persistently asking for ways programs, such as UHC, to operationalize the human rights framework in all domains of development. Mostly, this has meant expensive international conferences are now devoted to the discussion and elaboration of UHC. But there is much ambiguity regarding this concept. In its earliest conception, UHC was about creating unified, comprehensive, publicly funded healthcare systems. In the current climate - dominated by neoliberal ideologies - the discussion is focused on offering patients "choices." Having choices is important, but the choices offered to patients occur in a particular political and economic environment and they are not politically neutral. The powers-that-be have exploited the ambiguities surrounding the term "UHC." Instead of promoting a unified, comprehensive public system, the focus is on creating a healthcare market driven by (mainly) private insurance companies. Such markets commodify health and are an anathema to those of us who see health as a human right. (Turiano and Smith 2008)